Herpetofauna Diversity at Munggu Village, Landak Regency, West Kalimantan Province, Indonesia - Maulidi, Andri; Jakaria, Mohamad; Fitriyana, Nurul; Rizki, Muhammad (Department of Biology, Faculty of Sci and Tech, Universitas Islam Negeri Alauddin Makassar, 2019)
A large number of forests at Munggu Village, Ngabang District, Landak Regency have been converted into oil palm and rubber plantations. As consequences, natural habitats in the region have been fragmented and species diversity, including herpetofauna, has been decreased. This study aimed to assess herpetofauna diversity in four different habitats in Munggu Village: (1) forests, (2) Landak river, (3) tourist areas, and (4) rubber plantations. Data collection used Visual Encounter Survey (VES) for 8 days.[u1] The results showed that the total of 24 herpetofauna species: 15 amphibians’ species (4 families) and 9 reptiles species (6 families) have been recorded from the four sampled areas. Of the four locations 11 species were found in river habitat in the forest, 4 species in the location of Landak river, 8 species in tourism sites and 9 species in rubber plantations. The Shannon-Wiener (H') diversity index in all four habitats was classified as moderate. In the river location in the forest, H' was 2.14, in the Landak river it was 1.28, in the tourism sites it was 1.71 and in the rubber plantation it was 1.87. However, the evenness index (E) for the herpetofauna community in all four locations was >0.80. Habitat loss and habitat destruction are among the causes of decline in amphibian and reptile populations. Knowing the diversity of herpetofauna, it is hoped that the community and stakeholders can collaborate to secure the herpetofauna in Munggu Village.